Penerapan Sistem Cloud Computing Dalam Meningkatkan Efisiensi Kerja Pada Organisasi Kesatuan Aksi Mahasiswa Sibolga Tapteng (KAMISTA) dengan Menggunakan Layanan Google Drive - Sabrina Putri; Adhe Eva Yolanda; Haryati; Ayulia Indah Utami; Rizka Anisa Putri; Alwi Alwilo Haryada (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2023)
Application of cloud computing systems in increasing work efficiency in the Sibolga Tapteng Student Action Unit (KAMISTA) organization. We use the Google Drive cloud computing service as a platform to implement the system. The purpose of this study is to evaluate how the application of a cloud computing system can improve work efficiency at KAMISTA.The research method we use is descriptive qualitative, conducting a survey of KAMISTA members to find out the level of use of the cloud computing system before and after implementing the system. We also collect data on the time needed by KAMISTA members to complete tasks before and after system implementation.The results show that there is a significant increase in work efficiency after the implementation of the cloud computing system. KAMISTA members show improvements in the speed of completing tasks and reducing the time it takes to search and access data. In addition, there has been an increase in collaboration and communication between KAMISTA members after the implementation of the system.Based on the results of this study, other organizations can also implement cloud computing systems to improve their work efficiency. And in this KAMISTA organization to continue to develop and increase the use of cloud computing systems to obtain greater benefits.